Business model development for a board game café at gading serpong, Tangerang - Hosana, Lifiester; Dung Do, Anh (The Indonesian Journal of Business Administration, 2018)
Abstract – This final project is about the business model development of Games On Café (G.O.C), a recently founded board game café located at Gading Serpong, Tangerang. Its business is a combination of café and interactive games. The business situation analysis covers the external environment, the internal environment and the financial analysis. PESTEL and Porter’s Five Forces are used as tools to analyze the external environment analysis, whereas the internal factors are examined by using value chain analysis. Based on the result of primary data collection, combined with the literature study, the author identifies G.O.C to adopt the differentiation focus strategy, according to Porter’s generic strategies. Having defined the generic strategies, the comprehensive business strategy is further developed by using business model canvas. Furthermore, the financial feasibility analysis is done using NPV, IRR, and payback period.Keywords: board games café, PESTEL, Porter’s Five Forces, business model canvas, NPV, payback period